PJOK TEACHERS’ PERCEPTIONS OF STUDENT PERFORMANCE INTRODUCTION TO THE SCHOOL FIELD (PLP) SPORTS EDUCATION DEPARTEMEN, RIAU UNIVERSITY IN 2023: CASE STUDY AT PEKANBARU CITY VOCATIONAL SCHOOL - Deri Aprilisasi; Kristi Agust; Muhammad Imam Rahmatullah (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to determine the Perception of Physical Education Teachers on the Performance of Students of the Introduction to School Fields (PLP) Department of Sports Education, University of Riau in 2023: Case Study at SMK Pekanbaru City. This study is a quantitative descriptive study using a survey method. The sample in this study was 20 Physical Education teachers, both male and female teachers spread across 10 Mitra SMKs. The research instrument was a research questionnaire consisting of 40 statements. The data analysis technique used descriptive analysis which was expressed in the form of a percentage. The results of the study indicate that the Perception of Physical Education Teachers on the Performance of Students of the Introduction to School Fields (PLP) Department of Sports Education, University of Riau in 2023: Case Study at SMK Pekanbaru City is included in the sufficient category with a large percentage of 50%, namely the majority of Physical Education teachers who gave perceptions were 10 people. In the good and less categories with the same percentage of 25% or 5 Physical Education teachers who gave perceptions. Meanwhile, the results of the categories of each indicator include pedagogical competence, the majority are in the sufficient category with a large percentage of 60% or 12 Physical Education teachers who gave perceptions, social competence, the majority are in the sufficient category with a large percentage of 75% or 15 Physical Education teachers who gave perceptions, personality competence, the majority are in the sufficient category with a large percentage of 65% or 13 Physical Education teachers who gave perceptions, and professional competence, the majority are in the sufficient category with a large percentage of 70% or 14 Physical Education teachers who gave perceptions. Thus, it can be concluded that the Perception of Physical Education Teachers on the Performance of Students of the Introduction to School Fields (PLP) of the Department of Sports Education, University of Riau in 2023: Case Study at SMK Pekanbaru City is categorized as sufficient.